THE INFLUENCE OF THE RAINY AND DRY SEASON ON THE QUALITY OF BALI CATTLE SEMEN AT THE BATURITI ARTIFICIAL INSEMINATION CENTER, TABANAN, BALI - Bebas, Wayan; Gorda, I Wayan; Dada, Ketut Anom (Buletin Veteriner Udayana, 2021)
This study aims to determine the effect of the rainy season and the dry season on the quality of Bali cattle sperm at the Baturiti Artificial Insemination Center, Tabanan, Bali. In an effort to support artificial insemination programs, accelerate genetic quality improvement, increase production to maintain national food security. This study used a completely randomized design with two variables: the rainy season (February - May 2019) and the dry season (June - September 2019). This study used 9 Bali cattle bull with a range of 5-8 years. The semen is collected using the artificial vaginal method, carried out twice a week for each bull. The observed variables included pH, volume (ml), color, thickness, mass movement, concentration (10 6 cells/ml), motility of spermatozoa (%), abnormality (%), and intact plasma membrane (%). The results were analyzed by T-test. The results of the study concluded that the season had no significant effect (P> 0.05) on the quality of Bali cattle’s semen at the Baturiti Artificial Insemination Center, Tabanan, Bali.